(untitled) (Raparin Journal of Humanities (RJH), 2020)
In this study, we showed the effect of psychiatric illnesses including depression and schizophrenia. Based on data obtained from Sulaymaniah city’s weather station’s records from the year 2009 to 2019. The data for the psychological illnesses were obtained from Sulaymaniah Directorate for psychological illnesses from 2009-2019 using SPSS-14. We revealed that weather conditions affect the incidence of these diseases at a rate of (81.3%) Furthermore, the effects were analyzed based on their correlation and the correlation coefficient was determined for each of the weather elements. Temperature is a positive factor that affects depression at a rate of (33.7%). While sun light positively affects schizophrenia at a rate of (15.7%) conversely among the negative factors, raining is the most common factor that affects depression at a rate of (43.5%). In addition, clouds negatively affect schizophrenia at a lower rate which is (21.3%).